A new panel of SNPs to assess thyroid carcinoma risk: a pilot study in a Brazilian admixture population. Issue 1 (December 2017) - dos Santos, Isabelle; Genre, Julieta; Marques, Diego; da Silva, Ananília; dos Santos, Jéssica; de Araújo, Jéssica; Duarte, Victor; Carracedo, Angel; Torres-Español, Maria; Bastos, Gisele; de Oliveira Ramos, Carlos; Luchessi, André; et al.
Abstract Background Thyroid cancer is a common malignant disease of the endocrine system with increasing incidence rates over the last few decades. In this study, we sought to analyze the possible association of 45 single nucleotide polymorphisms (SNPs) with thyroid cancer in a population from Rio Grande do Norte, Brazil. Methods Based on histological analysis by a pathologist, 80 normal thyroid specimens of tissue adjacent to thyroid tumors were obtained from the biobank at the Laboratory of Pathology of Liga Norte Riograndense Contra o Câncer, Natal, RN. Patient samples were then genotyped using the MassARRAY platform (Sequenon, Inc) followed by statistical analysis employing the SNPassoc package in R program. The genotypic frequencies of all 45 SNPs obtained from the International HapMap Project database and based on data from the ancestral populations of European and African origin were used to compose the control study group. Results In our study, the following 9 SNPs showed significant differences in their frequency when comparing the study and control groups: rs3744962, rs258107, rs1461855, rs4075022, rs9943744, rs4075570, rs2356508, rs17485896, and rs2651339. Furthermore, the SNPs rs374492 C/T and rs258107 C/T were associated with a relative risk for thyroid carcinoma of 3.78 (p  = 6.27 × 10e−5 ) and 2.91 (p  = 8.27 × 10e−5 ), respectively, after Bonferroni's correction for multiple comparisons. Conclusions These nine polymorphisms could be potential biomarkers of predisposition to thyroid carcinoma in the population from Rio Grande do Norte. However, complementary studies including a control group with samples obtained from healthy subjects in Rio Grande do Norte state, should be conducted to confirm these results.